Counselling and Training of Nutritional Snacks Making for Immunity Increasing During Covid 19 Pandemic - Siahaan, Ginta; Manalu, Mincu; Rumida; Ginting, Riska S; Manurung, Aprianti; Sihombing, Loika; Farida, Farida; Akmal, Ahmad RI (Journal of Saintech Transfer, 2022)
Increasing body immunity is very necessary after the Covid-19 pandemic. One of the efforts that can be made to increase the body's immunity is to consume functional foods with immunostimulant activity, such as processed snakehead fish products in the form of nuggets, and "parkusel" juice made from a mixture of bitter melon, dates and celery. The purpose of community service is to provide knowledge and skills to housewives and the community at the Veteran ABRI Housing Complex in Medan Estate, Deli Serdang Regency, in making functional food products in the form of snakehead fish nuggets and Perkusel juice. The community service method used is the counseling method with leafet aids and training in making snakehead fish nuggets and perkusel juice. The results of the activity showed that there was an increase in the knowledge of the community participants in community service activities about nutritious snack products that can increase body immunity by 71% in the good value category.